Metrical Reinterpretations in Ursula Mamlok's Panta Rhei, IV (1981) - Prevost, Roxane (Canadian University Music Review / Revue de musique des universités canadiennes, 2003)
Although composer Ursula Mamlok (b. 1928) has gained prominence in the areas of performance, recording, and publishing, her music has been largely neglected by scholars. This paper focuses on the fourth movement of her popular trio Panta Rhei (1981), specifically on the return of a distinctive repeated-note unit at the beginning and throughout the refrains. Mamlok varies the entries of the repeated-note unit so that perceived accelerations and decelerations, as described by Christopher Hasty, occur. By completing projections early or late, Mamlok's work gives the impression of "time in flux" or Panta Rhei.